Residual oil derived nitrogen-doped carbon-loaded intermetallic compound catalyst as well as preparation method and application thereof
By synthesizing a platinum-based binary intermetallic compound catalyst on petroleum residue-derived nitrogen-doped mesoporous carbon, the problem of preparing small-sized platinum-based intermetallic compounds in the prior art is solved, and a high dispersion and anti-sintering catalyst is achieved, which significantly improves the catalytic activity and stability in fuel cells.
Patent Information
- Application Number
- CN202311362877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
It is difficult to effectively prepare small-sized platinum-based intermetallic compound catalysts in the prior art, and they have problems of insufficient activity and poor stability in fuel cells.
By mixing petroleum residue-derived nitrogen-doped mesoporous carbon with metal precursors, and after heat treatment and reduction treatment, a platinum-based binary intermetallic compound catalyst is formed with residual oil-derived nitrogen-doped carbon-supported platinum-based binary intermetallic compound catalyst. The π electrons of the aromatic-rich ring interact with the d-π of the metal precursor to form a uniform mixture to prevent the agglomeration of intermetallic compounds, thereby preparing small-sized intermetallic compounds over a wide temperature range.
A small size (2.5-5nm) highly dispersed and sintered platinum-based intermetallic compound catalyst is prepared within a wide temperature range, which significantly improves the catalytic activity and stability, and is suitable for oxygen reduction reactions in fuel cells.
Smart Images

Figure CN119864436A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a residual oil-derived nitrogen-doped carbon-loaded intermetallic compound catalyst, a preparation method thereof, and an application thereof in fuel cell electrocatalytic oxygen reduction. Background Art
[0002] PEMFCs are one of the ideal power sources with high efficiency and cleanliness, but the ORR reaction occurring at the cathode is highly dependent on expensive commercial Pt / C catalysts. At the same time, existing commercial Pt / C catalysts still have the problems of insufficient activity and poor stability under long cycles. PtM intermetallic compounds formed by alloying Pt with three-dimensional transition metals M (M = Co, Fe and Cu, etc.) can significantly improve the catalytic activity and stability of ORR. However, the conversion of disordered alloys into ordered intermetallic compounds requires overcoming kinetic barriers to achieve atomic migration, and often requires high-temperature annealing, which inevitably leads to the Ostwald ripening effect and is not conducive to the exposure of the catalytically active surface. Therefore, the preparation of small-sized platinum-based intermetallic compounds remains a challenge.
[0003] At present, many strategies have been developed to prepare small-sized platinum-based intermetallic compounds, including shell protection, metal-organic framework (MOF) confinement, and electrostatic adsorption. However, these strategies usually require cumbersome preparation processes and are limited by the types of elements. In addition, carbon supports can be used to support platinum-based catalysts to control the growth of metal particles and regulate the metal electronic structure by forming high-strength Pt-C interactions. Therefore, the development of a simple and suitable synthesis method for large-scale production, especially the direct synthesis of small-sized intermetallic compounds on carbon supports and the enhancement of the sintering resistance and dispersibility of metals needs further study.
[0004] Petroleum vacuum residue is composed of a large number of graphene fragments and organic polymers connected and cross-linked with each other, mainly sp 2 C is the main component, which has the advantages of high carbon content, rich ingredients and easy functionalization. Such a carbon-rich network structure has a large number of π electrons, which easily produce strong electronic interactions with metal particles. There are few studies on using the rich π sites and diverse chemical environments in residual oil to construct catalyst supports and prepare highly dispersed and sintering-resistant metal compound catalysts through stronger Pt-C interactions with metals. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a residual oil-derived nitrogen-doped carbon-loaded intermetallic compound catalyst and a preparation method thereof. The residual oil-derived nitrogen-doped carbon provided by the present invention and the platinum-based intermetallic compound have a Pt-C bond, and the catalyst has the characteristics of small size, high dispersion and anti-sintering. The catalyst maintains excellent activity and stability in the cathode oxygen reduction reaction, and also shows good working condition practicality in the test of the proton exchange membrane electrode.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst, comprising: residual oil-derived nitrogen-doped mesoporous carbon and a platinum-based binary intermetallic compound (Pt x M y ). First, the residual oil-derived nitrogen-doped mesoporous carbon and the metal precursor are mixed and dispersed in a solvent, and an initial mixture is obtained after drying. The initial mixture is then heat-treated and reduced to obtain an intermetallic compound composite material; the present application utilizes the residual oil rich in aromatic rings to synthesize a carbon carrier with a large π conjugated system, and the d-π interaction between the π electrons and the metal precursor enables the precursor stage to form a uniform mixture; the introduction of nitrogen elements for anchoring and mesoporous confinement prevents further agglomeration of the precursor when generating intermetallic compounds; the above strategy can ultimately achieve the expected small-sized intermetallic compounds within a wide temperature range. It is characterized in that: the second metal element M forming the platinum-based binary intermetallic compound is any one of Co, Fe and Cu, the molar ratio of platinum to the second metal element M is 1:1, 1:3 and 3:1, the average particle size of the intermetallic compound is 2.5-5nm, the loading amount of platinum on the carrier is 15-26wt%, and the carrier forms a Pt-C bond with the platinum-based intermetallic compound.
[0008] The present invention also provides a method for preparing a residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst, comprising the following steps:
[0009] A. Disperse petroleum residue oil and ferric oxide template in a mass ratio of 1:4 in petroleum ether, stir thoroughly and dry to obtain a solid mixture. Under argon or nitrogen atmosphere, first increase the temperature to 250-350°C at a heating rate of 3°C / min, keep warm for 45-80 minutes, then continue to heat to 700-900°C at a rate of 3°C / min, and keep warm for 100-150 minutes. Use 2mol / L hydrochloric acid to remove the template, wash and grind to obtain residual oil mesoporous carbon material; dissolve the carbon material and urea in anhydrous ethanol and deionized water respectively, dry and grind, and obtain residual oil-derived nitrogen-doped mesoporous carbon after high-temperature treatment at 700-900°C for 100-150 minutes;
[0010] B. Disperse the nitrogen-doped mesoporous carbon derived from residual oil, aqueous chloroplatinic acid solution and a second metal salt precursor in deionized water and mix them ultrasonically, and then dry to obtain an initial mixture; place the initial mixture in an atmosphere of 5% hydrogen / 95% argon, and perform a reduction treatment at 200-350°C for 1-3 hours with a heating rate of 2-10°C / min; then heat it a second time to 600-900°C at a heating rate of 2-10°C / min and keep it warm for 1-4 hours to obtain a platinum-based binary intermetallic compound catalyst; place the obtained intermetallic compound catalyst in sulfuric acid with a concentration of 0.3-1.0 mol / L, and etch away the transition metal on the surface for 3-5 hours.
[0011] Furthermore, in step A, the mass concentration of the petroleum ether solution of petroleum residue oil is 0.02-0.04 g / mL, the mass concentration of the petroleum ether solution of the template agent is 0.08-0.16 g / mL; the mass concentration of the residual oil mesoporous carbon ethanol solution is 0.01-0.03 g / mL, the mass concentration of the urea aqueous solution is 0.14-0.42 g / mL; the mass ratio of the carbon source to the nitrogen source is 1:3-1:7.
[0012] Furthermore, in step B, the second metal salt is one of cobalt chloride hexahydrate, ferric chloride hexahydrate and cupric chloride dihydrate; and the molar ratio of platinum to the second metal element M is 1:1, 1:3 and 3:1.
[0013] The intermetallic compound catalyst provided in the present application can be prepared by impregnation and heat treatment, the method is universal for a variety of metals, and the process operation is simple and easy. Also provided is the application of the residual oil-derived nitrogen-doped carbon-loaded intermetallic compound catalyst in oxygen reduction and proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the X-ray diffraction pattern (XRD) of the residue oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst provided in Example 1 of the present invention.
[0015] Figure 2 Transmission electron microscopy (TEM) image and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst provided in Example 1 of the present invention.
[0016] Figure 3 The X-ray absorption spectrum (XAS) of the carbon-K edge of the residual oil-derived nitrogen-doped carbon before and after loading the PtCo intermetallic compound provided in Example 1 of the present invention.
[0017] Figure 4This is the Fourier transform extended X-ray absorption fine structure spectrum (FT-EXAFS) of the platinum-L3 edge in the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound provided in Example 1 of the present invention.
[0018] Figure 5 Cyclic voltammetry (CV) curves of the initial and 30,000-cycle stability of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound prepared in Example 1 of the present invention. Test process: 2 mg of the catalyst was dispersed in 600 μL of deionized water, 380 μL of ethanol and 20 μL of Nafion solution (5 wt%), and ultrasonicated for 1 h to obtain a catalyst ink. A certain volume of ink was dropped on a rotating disk electrode with a diameter of 5 mm and rotated to dry at a speed of 500 rpm. The CV test was carried out in 0.1 M HClO4 saturated with N2, with a scan range of 0 V to 1.2 V (vs RHE) and a scan rate of 50 mV / s. The stability test was carried out in 0.1 M HClO4 saturated with N2, with a CV range of 0.6 V to 0.95 V (vs RHE), a scan rate of 100 mV / s, and a scan number of 30,000 cycles.
[0019] Figure 6 Linear polarization curves (LSV) of the initial and 30,000-cycle stability test of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound prepared in Example 1 of the present invention. Test process: The LSV test was carried out in O2-saturated 0.1M HClO4, with a scan range of 0.1V to 1.1V (vs RHE) and a scan rate of 10mV / s.
[0020] Figure 7 This is the XRD pattern of the residual oil-derived nitrogen-doped carbon-supported Pt3Fe intermetallic compound catalyst provided in Example 2 of the present invention.
[0021] Figure 8 TEM and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported Pt3Fe intermetallic compound catalyst provided in Example 2 of the present invention.
[0022] Fig. 9 This is the XRD pattern of the residual oil-derived nitrogen-doped carbon-supported PtCu3 intermetallic compound catalyst provided in Example 3 of the present invention.
[0023] Fig.10 TEM and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported PtCu3 intermetallic compound catalyst provided in Example 3 of the present invention. DETAILED DESCRIPTION
[0024] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. Obviously, the described examples are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] (1) 2.5 g of Kuwait vacuum residue oil and 10 g of ferric oxide were mixed and dispersed in 80 mL of petroleum ether and mechanically stirred for 3 h at a stirring rate of 800 rpm. After stirring, the solvent was removed by rotary evaporation to obtain a uniform mixture; the obtained mixture was transferred to a quartz crucible or a corundum crucible, placed in a tubular furnace, and then nitrogen was introduced as a protective gas. The tubular furnace was heated to 300 ° C at a rate of 3 ° C / min and kept warm for 1 h, and then heated to 800 ° C at a rate of 3 ° C / min and kept warm for 2 h; then naturally cooled to room temperature, and the tubular furnace was maintained at normal pressure; then the obtained powder was transferred to a beaker, and a volume of 100 mL and a concentration of 2 mol / L hydrochloric acid solution was added, and stirred for 12 h for acid etching. ; Finally, centrifuge, wash and dry to obtain residual oil-derived mesoporous carbon; take 0.3g of residual oil-derived mesoporous carbon and 1.5g of urea, dissolve them in 20mL of ethanol and 10mL of deionized water respectively, stir them thoroughly, dry and grind them to obtain a mixture; transfer the obtained mixture to a quartz crucible or a corundum crucible, put it into a tubular furnace, and then introduce nitrogen as a protective gas, heat the tubular furnace to 800℃ at a rate of 3℃ / min for nitrogen doping, and keep it for 2h; then naturally cool to room temperature, keep normal pressure in the tubular furnace, and obtain residual oil-derived nitrogen-doped mesoporous carbon;
[0027] (2) 80 mg of the obtained residual oil-derived nitrogen-doped mesoporous carbon, 40 mg of H2PtCl6·6H2O and 18.4 mg of CoCl2·6H2O were dispersed in 20 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tube furnace, argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tube furnace as a protective gas, the tube furnace was heated to 200°C at a rate of 5°C / min for reduction for 2 hours, and then the temperature was increased to 800°C at a rate of 5°C / min and kept warm for 2 hours; finally, it was naturally cooled to room temperature and the tube furnace was maintained at normal pressure to obtain a PtCo intermetallic compound catalyst; the obtained PtCo intermetallic compound catalyst was placed in sulfuric acid with a concentration of 0.5 mol / L and the etching time was 4 hours.
[0028] Figure 1 This is the XRD pattern of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst provided in Example 1 of the present invention. Figure 1As shown, the (001) and (100) characteristic diffraction peaks of the PtCo metal compound under this temperature condition are clearly visible. Figure 2 TEM and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst provided in Example 1 of the present invention. The PtCo intermetallic compound is uniformly distributed on the residual oil-derived nitrogen-doped carbon, and the average particle size is 2.58±0.05 nm. Figure 3 The XAS spectra of the carbon-K edge of the residual oil-derived nitrogen-doped carbon before and after loading the PtCo intermetallic compound provided in Example 1 of the present invention are shown in FIG. Figure 3 As shown in the figure, four characteristic peaks appeared before and after the PtCo intermetallic compound was loaded on the residual oil-derived nitrogen-doped carbon, corresponding to the dipole moment transitions of π*C=C (285.4 eV), π*CN (286.9 eV), π*C=O (288.5 eV) and σ*CC antibonding states. After the PtCo intermetallic compound was loaded, the intensity of the π* characteristic peak of the residual oil-derived nitrogen-doped carbon decreased significantly, indicating that the π site of C as the anchoring site has formed a metal-C bond, and the C atom has obtained electrons from the metal, resulting in a decrease in the number of C 2pπ unoccupied states. Figure 4 This is the FT-EXAFS spectrum of the platinum-L3 edge in the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound provided in Example 1 of the present invention. Figure 4 As mentioned above, Pt-L3 edge and The scattering peaks at 240 nm and 240 nm correspond to Pt-C and Pt-Pt / Co coordination, respectively. The generation of Pt-C bonds confirms the strong d-π interaction between the carbon support and Pt atoms. Figure 5 The CV curves of the initial and 30,000-cycle stability of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound prepared in Example 1 of the present invention show that the initial electrochemically active surface area (ECSA) is 83.8 m 2 / g Pt After 30,000 stability cycles, the ECSA decreased slightly, indicating that the highly ordered PtCo intermetallic compound catalyst has good stability. It also shows that the PtCo intermetallic compound has no obvious agglomeration and shedding phenomenon, and the carrier has a strong anchoring effect on the PtCo intermetallic compound. Figure 6 The initial and 30,000-cycle stability LSV curves of the residual oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound prepared in Example 1 of the present invention show that the initial mass activity (MA) is 1.77 A / mg. PtAfter 30,000 stability cycles, the MA loss was 24.3%, and the MA after the loss was still higher than the DOE target requirement. In addition, the half-wave potential only dropped by 18 mV, indicating that the residue-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst has excellent stability and excellent activity.
[0029] Example 2
[0030] (1) The steps are the same as those in Example 1;
[0031] (2) 40 mg of the obtained residual oil-derived nitrogen-doped mesoporous carbon, 20 mg of H2PtCl6·6H2O and 3.5 mg of FeCl3·6H2O were dispersed in 10 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tubular furnace, and argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas. The tubular furnace was heated to 200°C at a rate of 4°C / min for reduction for 2 hours, and then heated to 900°C at a rate of 4°C / min for 2 hours; finally, it was naturally cooled to room temperature and the tubular furnace was maintained at normal pressure to obtain a Pt3Fe intermetallic compound catalyst; the obtained Pt3Fe intermetallic compound catalyst was placed in sulfuric acid with a concentration of 0.3 mol / L and the etching time was 3 hours.
[0032] Figure 7 The XRD diagram of the residual oil-derived nitrogen-doped carbon-supported Pt3Fe intermetallic compound catalyst provided in Example 2 of the present invention, the Pt3Fe intermetallic compound corresponds one to one with the characteristic peaks in the PDF card, indicating the successful synthesis of the Pt3Fe intermetallic compound phase. Figure 8 TEM and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported Pt3Fe intermetallic compound catalyst provided in Example 2 of the present invention, the average particle size of Pt3Fe is 3.74±0.09nm.
[0033] Example 3
[0034] (1) The steps are the same as those in Example 1;
[0035] (2) 80 mg of the obtained residual oil-derived nitrogen-doped mesoporous carbon, 40 mg of H2PtCl6·6H2O and 39.5 mg of CuCl2·2H2O were dispersed in 10 mL of deionized water and ultrasonically dispersed for 1 hour. After rotary evaporation and drying, a uniformly mixed precursor was obtained; the precursor was placed in a tubular furnace, and argon hydrogen (volume fraction of 95% Ar + 5% H2) was introduced into the tubular furnace as a protective gas. The tubular furnace was heated to 200°C at a rate of 6°C / min for reduction for 3 hours, and then heated to 600°C at a rate of 6°C / min and kept warm for 2 hours; finally, it was naturally cooled to room temperature and the tubular furnace was maintained at normal pressure to obtain a PtCu3 intermetallic compound catalyst; the obtained PtCu3 intermetallic compound catalyst was placed in sulfuric acid with a concentration of 1 mol / L and the etching time was 5 hours.
[0036] Fig. 9 The XRD pattern of the residual oil-derived nitrogen-doped carbon-supported PtCu3 intermetallic compound catalyst provided in Example 3 of the present invention shows that the PtCu3 intermetallic compound phase has been successfully synthesized. Fig.10 TEM and particle size statistical distribution diagram of the residual oil-derived nitrogen-doped carbon-supported PtCu3 intermetallic compound catalyst provided in Example 3 of the present invention, the average particle size of PtCu3 is 2.82±0.05nm.
[0037] Example 4
[0038] In order to test the performance of the catalyst in actual PEMFC operating conditions, the residual oil-derived nitrogen-doped carbon-loaded PtCo intermetallic compound catalyst provided in Example 1 was used for a single cell system test of a hydrogen-air fuel cell. Test method: The catalyst ink was sprayed on a 2.5 cm × 2.5 cm Nafion 211 membrane, and the gas diffusion layer (carbon paper) and the catalyst-coated proton membrane were pressed under a certain pressure by hot pressing to prepare a membrane electrode (MEA) assembly. The MEA anode was sprayed with 20 wt% Pt / C, and the cathode was sprayed with the prepared residual oil-derived nitrogen-doped carbon-loaded PtCo intermetallic compound catalyst. The Pt loadings of the cathode and anode were 0.2 and 0.1 mg / cm, respectively. 2 The test back pressure was 2atm, the measurement temperature was 80℃, and the anode and cathode were respectively fed with H2 and air with a humidity of 100%, with flow rates of 400mL / min and 1200mL / min. Before the test, the membrane electrode needs to be activated to completely activate the catalyst. After the fuel cell system is stable, the power density of the single cell is measured to be 808mW / cm 2 , indicating that the residue oil-derived nitrogen-doped carbon-supported PtCo intermetallic compound catalyst has good practical application performance.
[0039] In summary, the present invention provides a catalyst of a residual oil-derived nitrogen-doped carbon loaded with an intermetallic compound. The method has readily available raw materials, simple operation, and can achieve large-scale processing. The size of the loaded intermetallic compound is maintained at 2.5 to 5 nm, and has the characteristics of high dispersion and anti-sintering. The mesopores in the prepared residual oil-derived nitrogen-doped carbon can improve the material transfer rate in the catalytic reaction, so that it can maintain good activity and stability as a catalyst, and has good catalytic activity in acidic oxygen reduction reactions and application prospects of proton exchange membrane electrodes.
[0040] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst comprising: Residue oil-derived nitrogen-doped mesoporous carbon (NPPC) and platinum-based binary intermetallic compounds (Pt x M y ); the platinum-based binary intermetallic compound is directly loaded on the surface of nitrogen-doped mesoporous carbon derived from residual oil by a simple impregnation reduction method, and the NPPC forms a Pt-C bond with platinum.
2. The residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst according to claim 1, characterized in that: The second metal element M forming the platinum-based binary intermetallic compound is selected from one of Co, Fe and Cu, the molar ratio of platinum to the second metal element M is 1:1, 1:3 and 3:1, the average particle size of the intermetallic compound is 2.5-5 nm, and the loading amount of platinum on the carrier is 15-26 wt%.
3. A method for preparing the residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst according to claim 1, comprising the following steps: (1) mixing nitrogen-doped mesoporous carbon derived from residual oil, an aqueous solution of chloroplatinic acid, a second metal salt precursor and deionized water by ultrasonication, and drying to obtain an initial mixture; (2) subjecting the initial mixture of step (1) to a reduction treatment under a reducing atmosphere; and heating the mixture to a suitable temperature for a second time to obtain an intermetallic compound catalyst; (3) placing the intermetallic compound catalyst obtained in step (2) in sulfuric acid to etch away the transition metal on the surface; the sulfuric acid concentration is 0.3 to 1.0 mol / L; and the etching time is 3 to 5 hours.
4. The preparation method according to claim 3, characterized in that: The preparation method of the residual oil-derived nitrogen-doped mesoporous carbon described in step (1) is specifically as follows: petroleum residual oil and a ferric oxide template are mixed in petroleum ether, dried and pre-calcined, and the template is removed with hydrochloric acid to obtain a residual oil mesoporous carbon material; the carbon material and urea are dissolved in anhydrous ethanol and deionized water respectively, dried and subjected to high-temperature treatment to obtain residual oil-derived nitrogen-doped mesoporous carbon; the second metal salt precursor is one of cobalt chloride hexahydrate, ferric chloride hexahydrate and cupric chloride dihydrate.
5. The preparation method according to claim 4, characterized in that: The average particle size of the ferric oxide is 30-50nm; the mass ratio of the petroleum residue oil and the ferric oxide is 1:4; the mass ratio of the residual oil mesoporous carbon to urea is 1:3-1:7; the pre-calcination conditions are firstly to increase the temperature to 250-350°C at a heating rate of 3°C / min, keep the temperature for 45-80min, then to 700-900°C at a rate of 3°C / min, and keep the temperature for 100-150min; the high temperature treatment temperature of the nitrogen doping is 700-900°C, and the keeping time is 100-150min.
6. The preparation method according to claim 3, characterized in that: The reducing atmosphere in step (2) is 5% hydrogen / 95% argon, the reducing temperature is 200-350°C, the reducing time is 1-3h, and the heating rate is 2-10°C / min; the secondary heating temperature is 600-900°C, the holding time is 1-4h, and the heating rate is 2-10°C / min.
7. A residual oil-derived nitrogen-doped carbon-supported intermetallic compound catalyst Pt as claimed in claim 1 x M y Preparation method of / NPPC and its application in ORR and proton exchange membrane fuel cells (PEMFCs).
Citation Information
Cited By
High-dispersion platinum group metal-transition metal mesoporous carbon catalyst as well as preparation method and application thereof
CN121394437A